Aportación al catálogo de los gasteromicetes de Cataluña - Martín Esteban, María Paz; Vidal i Frigola, Josep Maria (Revista Catalana de Micologia, 2007)
Contribution to the catalogue of the Gasteromycetes from Catalonia (NE Spain). Three rare and interesting Gasteromycetes collected in Catalonia are here described and commented. The species discussed are the following: Bovista paludosa Lév . , Ileodictyon gracile Berk. y Lysurusmokusin (Cibot: Pers.) Fr.